An Orientation-Based Unification of Young Jetted AGN: The Case of 3C 286 - Berton, Marco; Foschini, Luigi; Caccianiga, Alessandro; Ciroi, Stefano; Congiu, Enrico; Cracco, Valentina; Frezzato, Michele; La Mura, Giovanni; Rafanelli, Piero (Frontiers in Astronomy and Space Sciences, 2017)
In recent years, the old paradigm according to which only high-mass black holes can launch powerful relativistic jets in active galactic nuclei (AGN) has begun to crumble. The discovery of $γ$-rays coming from narrow-line Seyfert 1 galaxies (NLS1s), usually considered young and growing AGN harboring a central black hole with mass typically lower than 10$^8$ M$_\odot$, indicated that also these low-mass AGN can produce powerful relativistic jets. The search for parent population of $γ$-ray emitting NLS1s revealed their connection with compact steep-spectrum sources (CSS). In this proceeding we present a review of the current knowledge of these sources, we present the new important case of 3C 286, classified here for the fist time as NLS1, and we finally provide a tentative orientation based unification of NLS1s and CSS sources.